An identification of deterioration on Kelingkan embroidery from the collection of Department of Museums Malaysia - Sharipuddin, Nirmala; Abdul Razak, Rajabi; Md. Sharif, Harlina (UMK Press, 2018)
Kelingkan embroidery is an art of embellishing a thin fabric like cotton voile, silk crepe or chiffon, with flat gilded metal threads of gold or silver. This traditional Malay embroidery was inherited and collected by its collectors from Malay regions particularly Peninsular Malaysia, Sarawak, Brunei and Indonesia. This research is dedicated to identify types of deteriorations occurred on these historical objects and factors that contribute to their deteriorations. The Kelingkan embroideries collection from the Department of Museum Malaysia has been chosen for this research. Various level of analyses; physical and microscopic analysis was carried out to identify the damages. The results identify common major damages as tears, loss parts, darkening of threads, stains, fading, discolouration and folded lines. While factors contributing to their deteriorations are aging, intricate motifs, the nature of materials, environmental conditions and chemical reactions, handling as well as approaches to storage and display system. This research intends to serve as guidance for further and deeper researches on the preservation of traditional textiles in Malaysia.